THE ROLE OF BLOCKCHAIN TECHNOLOGY IN STRENGTHENING THE SUPPLY CHAIN OF LOCAL AGRICULTURAL PRODUCTS - Mahidin Fahmie; Loso Judijanto (CV. Adiba Aisha Amira, 2025)
This research aims to analyse the role of blockchain technology in strengthening the supply chain of local agricultural products through a literature review. Blockchain as a decentralised recording technology offers transparency, security, and efficiency in every stage of the supply chain, from production, distribution, to consumption. With an immutable record system that can be accessed in real-time by all stakeholders, blockchain is able to minimise the risk of counterfeiting, increase consumer confidence, and automate the transaction process through smart contracts. However, the implementation of blockchain in the local agricultural sector still faces various challenges, such as limited digital infrastructure, low technological literacy among farmers, and the absence of supporting regulations. This research concludes that collaboration between the government, business actors, and the farming community is needed to optimise the potential of blockchain. The integration of blockchain with other technologies such as IoT and AI in the future is expected to create a more transparent, efficient, and sustainable agricultural ecosystem.